SARM1 detection in myelinating glia: sarm1/Sarm1 is dispensable for PNS and CNS myelination in zebrafish and mice - Fazal, Shaline V.; Mutschler, Clara; Chen, Civia Z.; Turmaine, Mark; Chen, Chiung-Ya; Hsueh, Yi-Ping; Ibañez-Grau, Andrea; Loreto, Andrea; Casillas-Bajo, Angeles; Cabedo, Hugo; Franklin, Robin J. M.; Barker, Roger A.; et al. (Frontiers in Cellular Neuroscience, 2023)
Since SARM1 mutations have been identified in human neurological disease, SARM1 inhibition has become an attractive therapeutic strategy to preserve axons in a variety of disorders of the peripheral (PNS) and central nervous system (CNS). While SARM1 has been extensively studied in neurons, it remains unknown whether SARM1 is present and functional in myelinating glia? This is an important question to address. Firstly, to identify whether SARM1 dysfunction in other cell types in the nervous system may contribute to neuropathology in SARM1 dependent diseases? Secondly, to ascertain whether therapies altering SARM1 function may have unintended deleterious impacts on PNS or CNS myelination? Surprisingly, we find that oligodendrocytes express sarm1 mRNA in the zebrafish spinal cord and that SARM1 protein is readily detectable in rodent oligodendrocytes in vitro and in vivo. Furthermore, activation of endogenous SARM1 in cultured oligodendrocytes induces rapid cell death. In contrast, in peripheral glia, SARM1 protein is not detectable in Schwann cells and satellite glia in vivo and sarm1/Sarm1 mRNA is detected at very low levels in Schwann cells, in vivo, in zebrafish and mouse. Application of specific SARM1 activators to cultured mouse Schwann cells does not induce cell death and nicotinamide adenine dinucleotide (NAD) levels remain unaltered suggesting Schwann cells likely contain no functionally relevant levels of SARM1. Finally, we address the question of whether SARM1 is required for myelination or myelin maintenance. In the zebrafish and mouse PNS and CNS, we show that SARM1 is not required for initiation of myelination and myelin sheath maintenance is unaffected in the adult mouse nervous system. Thus, strategies to inhibit SARM1 function to treat neurological disease are unlikely to perturb myelination in humans.